PENCATATAN PERKAWINAN DALAM UNDANG-UNDANG NOMOR 1 TAHUN 1974 TENTANG PERKAWINAN PERSPEKTIF HUKUM ISLAM - Umami, Hafidhul; Mudaí, Syaiful (USRATUNA: Jurnal Hukum Keluarga Islam, 2020)
Marriage is a very sacred thing considering that it can legalize the relationship between a man and a woman, but many parties consider marriage to be an ordinary bond as evidenced by rampant prostitution wrapped in abusive marriages or contract marriage. It is important to overcome such things by passing the Marriage Law number 1 of 1974 concerning marriage, one of which is related to marriage registration. Islamic law does not explicitly discuss marriage registration, considering that in early Islam (ancient times) there was not much prostitution engineering in the name of marriage, in modern times there has been a lot of such prostitution to anticipate the emergence of the law on marriage registration. Marriage registration which is a government regulation does not violate the provisions in Islamic law and even supports Islamic law. Because this can bring maslahah and reject madlarat. This is in accordance with the principles of Islamic law, namely paying attention to the benefit of humans.